PENERAPAN METODE SOSIODRAMA DALAM PENGUATAN SIKAP PEDULI SOSIAL DAN TOLERANSI BERAGAMA SISWA SMA LABSCHOOL UNESA - Azizah, Nur; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2024)
Abstract Social care attitudes and religious tolerance attitudes are still a problem at Labchool Unesa High School, so that through the application of sociodrama methods, it is hoped that social care attitudes and religious tolerance attitudes can be strengthened in students. This type of research is Experimental Quasy with a Nonequivalent Control Group Desaign design. A population of 169 students was obtained by using the probability sampling technique of 72 students consisting of class 11 Bikifimae 1 as many as 36 students as an experimental class and class 11 Bikifimae 2 as many as 36 students as a control class. The research variable is the application of the sociodrama method as a control variable, while the bound variable in this study is social care attitude and religious tolerance attitude. The data collection technique was carried out by means of observation and assessment of attitudes through self-assessment in the prettest and posttest. Data analysis was carried out with the help of SPSS Statistics version 23. The study was conducted using the Paired Samples t Test with the conducted using the Paired Samples t Test with the results of Asymp.Sig (2-tailed) of 0.013 < 0.05 for the variable of social care attitude and Asymp.Sig (2-tailed) of 0.00 < 0.05 for the variable of religious tolerance attitude, so that the results showed that Ha was accepted, meaning that through separate analysis it can be concluded that the application of the sociodrama method has a significant positive effect on strengthening social care attitudes and has a significant positive effect on strengthening religious tolerance attitudes in students at Unesa Labschool High School, so that the application of sociodrama methods can be used as an alternative in strengthening students' attitudes of social care and religious tolerance